HUBUNGAN KONDISI STUNTING DENGAN INDEKS KEPALA PADA ANAK USIA 10-12 TAHUN - fitri, haria; kasuma, nila; fajrin, fildzah; tomisha, sisi (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Stunting is a condition in which the length or height is less than the age. One of the causes is a lack of nutritional intake for a long time in the first 1000 days of life (HPK), which is a period of nutritional fulfillment that affects head growth. The process of head growth requires adequate nutrition. Disorders of brain development due to stunted head growth mean that there are differences in head shape that can be measured using the cephalic index. Aim: The purpose of this study was to determine the relationship between stunting and head index. Method: This type of research is an observational analytic study with a cross-sectional research design. The sample in this study consisted of two groups, and the size was calculated using an unpaired categorical analytic formula. The minimum sample size for two groups, namely stunted and normal children, was 50 children. Result: The results of this study showed a relationship between stunting conditions and head index in children aged 10–12 years with a value of p < 0.05. Conclusion: Inadequate nutrition results in deficient craniofacial growth and development.